Long-term Prospective Comparative Analysis of Ototoxic and Survival Outcomes of Sequential Boost and Simultaneous Integrated Boost of Volumetric Modulated Arc Therapy for Head-Neck Carcinomas - Nidhin Das; Sri Harsha Kombathula; Vidhu Sharma; Puneet Pareek; Kapil Soni; Amit Goyal (Turkish Archives of Otorhinolaryngology)
Objective: To compare the ototoxicity and survival in head and neck carcinoma patients treated with sequential (SEQ) and simultaneous integrated boost (SIB) of volumetric modulated arc therapy (VMAT). Methods: This long-term prospective study enrolled patients with histologically confirmed head and neck carcinoma, all receiving VMAT treatment. Audiological assessments were done using various tests at baseline, two weeks, treatment completion, six months, and 12 months. The changes in bone conduction pure tone thresholds were correlated with cochlear dose, comparing SEQ and SIB plans. We also investigated other significant late toxicities that led to dysphagia, voice changes, and xerostomia. Survival was assessed with the Kaplan-Meier analysis. Results: The study included 93 patients (186 ears), 40 receiving radiation alone and 53 undergoing chemoradiation. Baseline hearing levels for the right and left ears were 13.3±2.3 dB and 14.2±1.5 dB. After 12 months of radiation, levels were 18.5±2.4 dB and 19.11±1.9 dB, respectively. No significant changes were observed between SEQ and SIB plans, but high-frequency shifts occurred. The cochlea tolerated up to 28 Gy without hearing loss in the radiation-alone group but showed loss at 9 Gy when combined with cisplatin chemotherapy. The maximum dose (Dmax) and the mean dose (Dmean) of pharyngeal constrictor muscles predicted dysphagia. No significant SEQ vs. SIB differences were found in late toxicity or survival outcomes. Conclusion: Modern radiotherapy techniques like VMAT adhere to cochlear dose limits. No significant differences were found between SEQ and SIB plans in sensorineural hearing loss, late toxicity, or survival, making both suitable for head and neck carcinoma treatment.